Peningkatan Penguasaan Sains dan Teknologi Iran Pasca Embargo Amerika Serikat Tahun 2006 - Dinar Ashofi Wulandari Hernawa; Hikmatul Akbar (Jurnal Paradigma, 2013)
The aim of the research is to know; (1) What are the enhancements of science and technology in Iran Islam Republic after the embargo by United States in 2006; (2) What causes the increase of science and technology in Iran. This research using a method of qualitative, with the procedure data collection techniques based on facts. This research can be summed as follows: first, there are the discoveries of science and technology after embargo by the United States (after 2006). Second, the increase in science and technology its cause by natural resources factors and the ability of the economy and ability of the population and owned by the powerful ideology of the Iranian nation.